Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/jca.21252
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of unsuccessful mobilization with granulocyte colony‐stimulating factor alone in patients undergoing autologous hematopoietic stem cell transplantation

Abstract: Mobilization of hematopoietic stem cells is achieved with hematopoietic growth factors with or without chemotherapy or other agents. Although studies comparing granulocyte colony-stimulating factor (G-CSF) alone to combined regimens demonstrate an increase in stem cell yield in the latter, mobilization with G-CSF alone is still effective and has been widely practiced. We conducted a retrospective cohort study of consecutive patients at our institution who underwent at least one mobilization attempt with G-CSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Using chemotherapy and G‐CSF instead of G‐CSF only is not a guarantee that a donor will collect adequate numbers of CD34+ cells. A small number of donors will not collect adequate numbers of stem cells for HSCT . Out of 165 patients who were mobilized and collected, 27 were classified as poor mobilizers, 25.4% had lymphoma and 9.6% had multiple myeloma .…”
Section: Stem Cell Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using chemotherapy and G‐CSF instead of G‐CSF only is not a guarantee that a donor will collect adequate numbers of CD34+ cells. A small number of donors will not collect adequate numbers of stem cells for HSCT . Out of 165 patients who were mobilized and collected, 27 were classified as poor mobilizers, 25.4% had lymphoma and 9.6% had multiple myeloma .…”
Section: Stem Cell Mobilizationmentioning
confidence: 99%
“…Lymphoma diagnosis ( P = 0.001), advanced age ( P = 0.007), and increased weight ( P = 0.03) were identified as potential risk factors for poor mobilization . (Table ) A larger study by Chow et al , retrospectively evaluated 293 donors of which 251 were successfully mobilized. By univariate analysis, underlying disease, mobilization attempts, and number of previous chemotherapy regimens were risk factors for poor mobilization.…”
Section: Stem Cell Mobilizationmentioning
confidence: 99%
“…Factors that predict poor mobilization include underlying disease, involvement of bone marrow by metastatic disease and relapse . Treatment related factors include multiple lines of previous therapy, in particular marrow toxic agents such as purine analogs, mid‐cycle vincristine chemotherapy given prior to apheresis, and previous exposure to radiation . Factors related to the mobilization regimen include a higher yield with chemotherapy + G‐CSF than with G‐CSF alone and total G‐CSF dose .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that older age is associated with poorer stem cell mobilization 4 whereas others have found no influence of age on mobilization success. 5 …”
mentioning
confidence: 99%